Penalaran Berbasis Aturan Untuk Deteksi Dini Penyakit Kulit Akibat Infeksi Jamur - Risya Maulidyah; Ause Labellapansab; Akmar Efendi (Ikatan Ahli Informatika Indonesia, 2018)
The skin has an important role for the human body. The skin has a function of protection, absorption, and expression. Many do not know that some living creatures such as bacteria, viruses or fungi cause the onset of skin diseases. Fungal skin disease is a common skin disease in Indonesia. The symptoms are generally felt will cause discomfort in patients and late to know the diagnosis of disease and handling of the doctor will also cause the handling is not appropriate. Skin diseases of fungal infections can be known earlier by using the field of expert system science. This expert system consists of 25 diseases. From the acquisition of knowledge by an expert, found 82 symptoms and generate 25 rules (rules) are represented using the decision table. The search method uses forward chaining while to deal with the uncertainty that emerges is used certainty factor method from Mycin application. This system is built web-based to facilitate the user. Based on the tests conducted to prove that the expert system diagnosis of skin diseases of fungal infections are able to diagnose with a value of 94,28% accuracy value. With a known diagnosis of skin diseases that occur when the subscription will be done more quickly and precisely. expert system, forward chaining, certainty factor, skin